The Distribution of Aircraft Passenger Movements on Java Island Using the Gravity Model - Gunawan, Gunawan (Institut Teknologi Dirgantara Adisutjipto, 2018)
The need for movement always causes problems, especially when humans go to the same destination in a certain area at the same time. It is needed to do the analysis of the distribution of aircraft passenger movement in order to provide the required facilities in the future. This research model the distribution of aircraft passenger movements on Java Island using the Double Constrain Gravity model(DGCR) with the negative exponential, rank and tanner obstacle function. In this case, it is found that the Double Constrain Gravity Model (DGCR) with tanner obstacle function is the best method due to the smallest standard deviation. It could be concluded that the DCGR model with tanner obstacle functions is more accurate when compared to the DCGR model with other obstacle functions in estimating the movement distribution in 2025 on Java Island.